State of Scientific Research of Knowledge Management in the Republic of Kazakhstan - USKELENOVA, Assel T.; SHADIYEV, Kairatbek Kh.; KULAZHANOV, Yernur (Journal of Advanced Research in Law and Economics; Vol 8 No 8 (2017): JARLE, Volume VIII, Issue 8(30), Winter 2017, 2018)
Substantiated the necessity of developing the theoretical scientific basis for the development of the knowledge management system in the Republic of Kazakhstan (RK). The research directions of Kazakhstani scientists in the field of the knowledge economics are analyzed and theoretically generalized, and the limited nature of objects of research in the field of problems is argued. The main directions of the scientific search in the framework of knowledge management are revealed. This approach contributes to the objectivism and actualization of scientific research and promotes the theoretical and methodological basis formation for the development of the knowledge management system in the Republic of Kazakhstan.